ETNOMEDICINE STUDY: KATUK LEAVES (SAUROPUS ANDROGYNUS (L.) MERR.) FOR BREAST MILK BOOSTER IN SUMBERAN NGESTIHARJO KASIHAN BANTUL - Sri Budiarti, Nur Idha; Kintoko, Kintoko (International Journal of Islamic and Complementary Medicine, 2021)
Breastfeeding is very important for optimal growth and development for babies. One of the efforts that can be done to increase breast milk production is by using traditional ingredients such as katuk extract (Sauropus androgynus (L.) Merr.). This study aims to determine form of the herb, processing method, usage method and the factors behind people using katuk leaves (Sauropus androgynus (L.) Merr.) for breast milk booster in Sumberan Ngestiharjo Kasihan Bantul. The research method used is descriptive qualitative observation. The sampling technique was snowball sampling through observation and in-depth interviews with informants who knew about the use of katuk plants to increase breast milk production in Sumberan Village, then the informants selected respondents to provide additional information. The results showed that the form of katuk leaves (Sauropus androgynus (L.) Merr.) was as a vegetable, brewed, encapsulated and blended to extract the starch. The processing method is cooked as a vegetable, made juice to drink, boiled for fresh vegetables and dried, its use by eating with a frequency of two times a day used during breastfeeding. The factors behind people using katuk leaves to increase breast milk production that is believed katuk leaves can increase breast milk production or breast milk boosters at low prices and easy to obtain. Katuk leaves (Sauropus androgynus (L.) Merr.) to increase breast milk production, which can be consumed as a vegetable by eating it with a frequency of two times a day during breastfeeding. The factors behind people using katuk leaves (Sauropus androgynus (L.) Merr.) that katuk leaves are believed to increase breast milk production.